TRATEGI RRI PRO 2 SURAKARTA DALAM MENARIK MINAT PENDENGAR MUDA - Arifatama, Wardhana; Kartinawati, Erwin; Wiryawan, Hari (JURNAL KOMUNITAS, 2022)
This study aims to describe how the strategy used by RRI Pro 2 Surakarta in attracting listeners, especially young listeners. The method in this research is descriptive, using a qualitative approach. Based on the results of the study and discussion, it can conclude that RRI Pro 2 Surakarta broadcasts on 105.5 FM have the power to develop strategies to attract listeners, namely, by 1) utilizing a wide broadcast range, 2) from the aspect of broadcast programs, RRI Pro 2 Surakarta using a clock format system that distinguishes morning, afternoon, evening, and night activities whose composition adjusts to the listener's lifestyle at certain hours, 3) from the contents of the RRI Pro 2 Surakarta program, some agendas are packaged by involving listeners, 4) in an approach through On social media, RRI Pro 2 Surakarta utilizes the WhatsApp Blast system, a system where RRI Pro 2 Surakarta sends the theme of the event to be discussed to listeners whose contacts are on Pro 2 FM, 5) holds on-air and off-air activities involving listeners. Apart from these five aspects, another strategy for RRI Pro 2 Surakarta to attract young listeners is to take advantage of existing opportunities to create exciting and valuable broadcast programs. That is part of the strategy in developing its broadcast targets.